Effects of droughtscreening methodology on genetic variances and covariances in Pool 16 DT maize population - Badu-Apraku, Baffour; Fakorede, M.A.B.; Menkir, A.; Kamara, A.; Adam, A. (Cambridge University Press, 2004)
North Carolina Design I (NCD I) progenies derived from Pool 16 DT, a white, dent, early maturing, drought-tolerant and streak resistant tropical maize (Zea mays L.) population, were evaluated in the 1995/96 and 1997/98 dry seasons, using two sites each season in Côte d'Ivoire. In all sites, the crop was irrigated from planting to about 2 weeks before anthesis; irrigation was discontinued thereafter for the rest of the season in one site (Soumis) in 1995 and both sites (Ferkessédougou and Sinematialli) in 1997. Irrigation was continued until maturity in the second site (Temoin) in 1995. In 1995, the additive component of genetic variance was much larger than the other components. The narrow-sense heritability estimate (h2) was 73% for grain yield and 43–71% for seven other traits. In 1997, only grain moisture at harvest, ear height, and days to anthesis and silking had positive additive genetic variances but the h2 were much lower (1·5–41%) than in 1995. Ears/plant, plant height and ear height had consistent positive correlation with grain yield; correlation of days to anthesis and silking date with yield were negative. Because of negative variances, additive genetic correlation could not be computed for most traits in 1997, but in 1995 grain moisture at harvest, plant height and ear height showed positive additive genetic correlation with yield. Other additive genetic correlation coefficients were low and/or not consistent. There is sufficient genetic variance to warrant continued selection for drought tolerance in Pool 16 DT. The induced stress, however, appears to be too severe to properly elicit the true differences among families and may, therefore, need to be modified.